Polyphenolic profile, antioxidant and neuroprotective potency of grape juices and wines from Fruška Gora region (Serbia) - Beara, Ivana N.; Torović, Ljilja D.; Pintać, Diandra Đ.; Majkić, Tatjana M.; Orčić, Dejan Z.; Mimica-Dukić, Neda M.; Lesjak, Marija M. (International journal of food properties, 2018)
This article reports novel and valuable data about three red (Cabernet Sauvignon, Frankovka and Merlot varieties), one rosé (Muscat Hamburg) and three white wines (Italian Riesling, Chardonnay and Sila), together with their related products (grape juices and young wines) produced in Fruška Gora vineyards, Serbia, concerning their in-depth polyphenolic profile and biological activities (antioxidant and neuroprotective). LC-MS/MS analysis of 47 phenolics showed that the phenolic acids, particularly ellagic (up to 8.99 mg/L, Cabernet Sauvignon) and caffeic acids (up to 2.83 mg/L, Frankovka) were generally more abundant in red wines. Also, the content of catechin and epicatechin (0.32-7.70 and 0.4-15.5 mg/L) as the leading flavonoids, malvidin 3-O-glucoside as the dominant anthocyanin (2.7-160 mg/L) or stilbene resveratrol (0.06-2.42 mg/L), were also higher in the red grape products. Overall antioxidant dominance of the red grape products, Merlot variety being the main one, was confirmed through several assays (DPPH * and * NO scavenging ability, reducing potential and inhibition of lipid peroxidation). In addition, grape juices and young wines, which are a good source of dietary natural antioxidants, were also evidenced. Furthermore, the optimised in vitro acetylcholinesterase inhibition assay was applied, indicating the grape juices and red wines as the most promising neuroprotective agents. Abbreviations: AAE: ascorbic acid equivalents; AChE: acetylcholinesterase; BHT: butylated hydroxytoluene; DPPH: 2,2-diphenyl-1-picrylhydrazyl; dw: dry weight; FA: fatty acids; FRAP: Ferric Reducing Antioxidant Power; LP: lipid peroxidation; MDA: malondialdehyde; SRM: selected reactions monitoring; PCA: principal component analysis; PG: propyl gallate; TBA: 2-thiobarbituric acid; TPTZ: 2,4,6-tripyridil-s-triazine.